THE INFLUENCE OF E-PROMOTION AND MARKET ORIENTATION THROUGH CUSTOMER LOYALTY ON COMPETITIVE ADVANTAGE AT MR.DIY PALANGKA RAYA - Putri Pebriani; Vivy Kristinae; Anike Retawati; Usup Riassy Christa (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to prove the influence of e-promotion on customer loyalty, the influence of e-promotion on competitive advantage, the influence of market orientation on customer loyalty, the influence of market orientation on competitive advantage, the influence of customer loyalty on competitive advantage, the influence of e-promotion on competitive advantage through customer loyalty, the influence of market orientation on competitive advantage through customer loyalty. Design/Methodology/Approach – Sample collection was carried out using SEM analysis techniques. The sample for this research is MR.DIY Palangka Raya customers. The data analysis used is structural model or inner model analysis with the SmartPLS version 3 application. Findings – The results of this research show that the e-promotion has a positive and significant effect on customer loyalty, e-promotion has a positive and significant effect on competitive advantage, Market Orientation has a positive and significant effect on customer loyalty, market orientation has a positive and significant effect on competitive advantage, customer loyalty has a positive and significant effect on competitive advantage, e-promotion has a positive and significant effect on competitive advantage through customer loyalty, market orientation has a positive and significant effect on competitive advantage through customer loyalty. Conclusion and Implications – The customer loyalty can mediate fully between e-promotion and market orientation on competitive advantage. MR.DIY can optimize the company's business accounts on relevant social media platforms such as Facebook, Instagram, Twitter and other social media.